2021
DOI: 10.1103/physrevfluids.6.014302
|View full text |Cite
|
Sign up to set email alerts
|

Fiber alignment in oscillating confined shearing flows

Abstract: Fiber orientation in oscillatory shearing flow was studied both experimentally and numerically. Optical measurements were made using a custom flow cell containing rigid, noncolloidal fibers suspended at high concentration in a Newtonian fluid. Simulations that account for hydrodynamic drag and excluded volume predict fiber alignment in the vorticity direction for some conditions, in agreement with the measurements. Vorticity alignment was found to be a complex function of strain amplitude and fiber concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…10b which compares the initial and final distribution of the fibers predicted by simulations. Note that the simulated values of S θ quantitatively matched the experimental results over a wide range of conditions (Strednak et al, 2021). Franceschini et al (2014) suggested that the transition in S θ and η'' is controlled by a critical effective volume fraction (Φ c ) of the suspension.…”
Section: Oscillatory Shearingsupporting
confidence: 65%
See 4 more Smart Citations
“…10b which compares the initial and final distribution of the fibers predicted by simulations. Note that the simulated values of S θ quantitatively matched the experimental results over a wide range of conditions (Strednak et al, 2021). Franceschini et al (2014) suggested that the transition in S θ and η'' is controlled by a critical effective volume fraction (Φ c ) of the suspension.…”
Section: Oscillatory Shearingsupporting
confidence: 65%
“…Measurements (Franceschini et al, 2011;Strednak et al, 2021) and simulations (Snook et al, 2012;Strednak et al, 2021) of the orientation distribution under oscillatory flows also demonstrate a remarkable transition in the alignment as a function of strain amplitude. As shown in Fig.…”
Section: Oscillatory Shearingmentioning
confidence: 80%
See 3 more Smart Citations